The significance of Team Time Management and Workplace Environment on rescue team performance during COVID-19 Pandemic / Norsyazwani Ab Halim, Shahrulnizam Nasir and Azlyn Ahmad Zawawi - Ab Halim, Norsyazwani; Nasir, Shahrulnizam; Ahmad Zawawi, Azlyn (2021)
The world has been hit with a strange and dangerous epidemic since the end of 2019. The pandemic started in Wuhan, China, and spread to the rest of the world, including Malaysia. The pandemic is known as Corona Virus (after that labeled as COVID-19). The first COVID- 19 case in Malaysia was confirmed on 25 January 2020, involving tourists from China arriving in Johor via Singapore (BH Online, 2020). The reported cases remained low and primarily limited to imported cases until several local clusters emerged in March 2020. The largest cluster at the time was associated with the Tabligh Congregational religious gathering held in Sri Petaling, Kuala Lumpur, in late February and early March, which led to a massive increase in local cases as well as the export of cases to neighboring countries (Yusmizal Dolah Aling & Hafidzul Hilmi Mohd Noor, 2021). Therefore, the Malaysian government, led by Tan Sri Muhyiddin Yassin, has implemented the Movement Control Order (MCO), which started on 18 March 2020 to reduce the spread of COVID-19 through social incarceration. To date, the total number of COVID-19 cases has exceeded 1 million cases (Official Website, Malaysian Ministry of Health, 2021).